The Relationship Between Knowledge of Anemia and School Support with Compliance in Iron (Fe) Tablet Consumption Among Female Adolescents at SMAN 1 Tirawuta, East Kolaka Regency - Zezylia Zezylia; Apriyanti Apriyanti; Hasniah Dina (Health & Medical Sciences, 2026)
Anemia remains one of the major public health problems among female adolescents worldwide and negatively affects physical growth, academic performance, productivity, and reproductive health. Iron (Fe) tablet supplementation has been implemented in Indonesia as an effective strategy to prevent iron deficiency anemia among adolescent girls; however, compliance with iron tablet consumption remains relatively low. This study aimed to determine the relationship between knowledge of anemia and school support with compliance in iron (Fe) tablet consumption among female adolescents at SMAN 1 Tirawuta, East Kolaka Regency. This quantitative study employed a cross-sectional design involving 132 female adolescents selected through proportional random sampling from a population of 198 students. Data were collected using a knowledge of anemia questionnaire, a school support questionnaire, and the Morisky Medication Adherence Scale (MMAS-8). Data analysis was performed using univariate and bivariate analyses with the Chi-Square test at a 95% confidence level (α = 0.05). The results indicated that 78.8% of respondents had good knowledge of anemia, 82.6% reported inadequate school support, and 71.2% were non-adherent to iron tablet consumption. Significant relationships were found between knowledge of anemia and adherence to iron tablet consumption consumption (p < 0.000) and between school support and compliance with iron tablet consumption (p = 0.006). The findings highlight the importance of strengthening health education and school-based support systems to improve adolescents' compliance with iron supplementation programs.